Findings of an International Research on the Future of Marketing Communication - Gábor Jr. Rekettye; Gábor Rekettye (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
The objective of the research was to map the most important global megatrends affecting the business and marketing environment and to analyze and understand how the changed environment will affect the practice and performance of marketing communication in the next decade. For identifying the global megatrends, a comprehensive literature review was initiated. For understanding the future changes in marketing communication an experts questionnaire survey was carried out in four countries – Croatia, Finland, Hungary, and India – in 2015. For the purpose of this paper, the data for Croatia, Hungary and India were picked out and analyzed. The research provided the possibility of comparing how experts and opinion leaders from the big emerging, and the two small transition countries evaluated the effects of the global megatrends on business environment, and how they thought the changed business environment would influence the future of marketing communication in their countries. The findings proved that the explored megatrends would have and important – however in the two regions differently evaluated – effect on marketing communication. The content, the used communication tools and the spending on marketing communication are the fields, which will influence the performance of the companies' marketing communication, and where radical changes are expected.
Keywords: M30; M31; M37; 330; global megatrends; business environment; development of marketing communication; future performance of marketing; management; market